2015
DOI: 10.3755/galaxea.17.15
|View full text |Cite
|
Sign up to set email alerts
|

First report of field sampling and identification of crown-of-thorns starfish larvae

Abstract: To date, field sampling and identification of the larvae of the coral-eating starfish Acanthaster planci have not been successfully performed (Birkeland 1990). We collected water samples (500 L) from 5 different depths (surface, 3 m, 7 m, 11 m, 15 m, and near the bottom) to find A. planci larvae on June 29, 2005, during the spawning period (Yasuda et al. 2010). The samples were obtained from Yabiji Reef, off Miyako Island, Okinawa, Japan (25°1′13.85″N, 125°14′49.20″E, Fig. 1A), where a population outbreak of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Moreover, genome sequencing of closely related species could provide a comparative genomic approach for population genomics and evolution within this group of animals. Other approaches such as eDNA could also serve as a tool to trace the distribution of early life stages of CoTS in the field [53,107,264]. These data will not only contribute to a better understating of CoTS genomics, but will also be required for effective conservation and management.…”
Section: Genetic and Genomic Samplingmentioning
confidence: 99%
“…Moreover, genome sequencing of closely related species could provide a comparative genomic approach for population genomics and evolution within this group of animals. Other approaches such as eDNA could also serve as a tool to trace the distribution of early life stages of CoTS in the field [53,107,264]. These data will not only contribute to a better understating of CoTS genomics, but will also be required for effective conservation and management.…”
Section: Genetic and Genomic Samplingmentioning
confidence: 99%
“…A flowmeter was calibrated during three replicate tows on an open frame (i.e., without a net). In a previous survey, more larvae were found at 7 m than at other depths, although there was a slight vertical distribution bias of A. planci larvae [19]. The volume of water filtered by the net was measured with a flowmeter (Rigo Co., Ltd., Tokyo, Japan) mounted at the net mouth.…”
Section: A Planci Larvae and Seawater Samplingmentioning
confidence: 99%
“…These primers can discriminate A. planci from a few common coral reef sea stars, such as Protoreaster spp., Linckia spp., and Culcita spp. [19].…”
Section: Identification Of a Planci Larvaementioning
confidence: 99%
“…These studies have indicated strong gene flow over a long distance along western boundary currents such as the Kuroshio Current region (genetic homogeneity from across the Ryukyu Islands to the temperate Pacific coast of mainland Japan, Yasuda et al, 2009) and the Eastern Australian Current region (the Great Barrier Reef, Nash et al, 1988; Benzie et al, 1999; Vogler et al, 2013; Harrison et al, 2017), while relatively limited gene flow and genetic differentiation were observed among distant Pacific islands (Yasuda et al, 2009; Timmers et al, 2012; Vogler et al, 2013). Overall, the studies found strong gene flow and genetic homogeneity in regions where strong currents are associated, although genetic data strongly reflect historical gene flow that was formed during past climate change, and the spatial extent of secondary outbreaks could be overestimated (Benzie 1999, Yasuda et al 2009, Yasuda et al 2015). Larval dispersal simulation studies in the Great Barrier Reef (GBR) have indicated southward larval dispersal along the Eastern Australian Current, which is consistent with historically observed patterns of secondary outbreaks of A. cf .…”
Section: Introductionmentioning
confidence: 91%
“…Miyake et al, 2009; Storlazzi et al, 2017), plankton-netting in the field (e.g. Yasuda et al, 2015; Suzuki et al, 2016), and drifting buoys (e.g. Fukuda and Hanamura, 1996), have been employed to estimate larval dispersal.…”
Section: Introductionmentioning
confidence: 99%